An investigation into the current and potential benefits of tourism-based development in the Albany and Peddie districts - Klinkradt, Mary Louise (Rhodes University, Faculty of Science, Department of Geography, 2003)
This research considers the relationship between tourism and development, and how tourism can be used as a means of promoting development. In order to explore this relationship, two districts in the Eastern Cape province of South Africa, the Albany and Peddie Districts have been selected as case study areas. Both the Albany and Peddie Districts are in need of development which can meet the economic and social development of the districts. One such option for the two districts is tourism-based development. This research examines the current status of tourism in both districts through the use of secondary data analysis and primary data gathered from questionnaires and interviews undertaken with tourists and representatives of key stakeholders in the tourism industry. This data was used to establish the current and future potential of tourism in the districts in terms of the availability and diversity of attractions and the tourism assets and facilities in the districts. It was also used to determine whether or not tourism, by promoting infrastructural and economic development, may lead to the socio-economic upliftment of the Albany and Peddie Districts. The results obtained from this research highlight the significant lack of tourism infrastructure in the Peddie District, and the reality that the tourism potential of the district remains untapped. With the marketing and promotion of tourism to the district, and the associated tourist requirements such as accommodation, and other facilities, tourism does hold a potential key to the socio-economic development of the district. The Albany District, however, has a well-established tourism industry, but the development spin-ofts are minimal, and the potential for further tourism-based development in the future would therefore appear to be somewhat limited. A GIS (Geographic Information System) was use to determine and detail possible tourism routes, a final outcome of the investigation being the proposal of two tourism routes to draw people into and through the study area, based on the current assets and attractions of the two districts. These routes highlight one of the options available in the districts to promote much needed development in the two districts through the use of the tourism industry.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Tourism -- South Africa -- Eastern Cape; Tourism -- South Africa -- Grahamstown; Tourism -- South Africa -- Peddie; Ecotourism -- South Africa -- Eastern Cape; Tourism -- South Africa -- Eastern Cape -- Management; Tourism -- Social aspects -- South Africa -- Eastern Cape